Pelatihan Entrepreuneurship Pada Pemuda Karang Taruna Batuang Sarumpun - Andre Ilyas; Nofritar Nofritar; Yuliarman Mahmudin (Konsienti : Community Services Journal, 2023)
Today's youth have received a qualified education. However, after graduating from school/college, youth still have the mindset of being a "job seeker". To change mindsets and motivate young people to become entrepreneurs, training is needed which is packaged in a community service activity conducted by a lecturer at the Putra Indonesia University "YPTK" Padang. The method for implementing Community Service activities consists of three stages of activity. The first stage of preparation includes pre-survey, team formation, preparation and submission of proposals, team and partner coordination and preparation of training tools and materials. The second stage is the screening stage, in the form of preparing speakers, ensuring complete supporting facilities and infrastructure, consumption, surprises and others. The third stage is the activity implementation stage. Providing material on the basics of becoming an entrepreneur, changing mindsets, developing youth interests and motivation to enter the world of entrepreneurship. After that, a discussion was held with the participants and it was revealed that the participants had begun to change their mindset and were eager to become entrepreneurs.